Leveraging the Synergistic Connectivity of Firebase Database for a Windows Desktop Clinic Management System and Android-based Mobile Incident Reporting - Amora, Norris Alexis Panganiban; Khan, Concepcion L. (International Journal of Computing Sciences Research, 2025)
Purpose – This study aims is to conduct case study testing and build synergistic connectivity of firebase database for a windows desktop-based clinic management system and an android based mobile incident reporting using firebase database. Method – The research design utilized was case study testing that will be constructed in the connectivity of firebase database in windows desktop application and android based application. It is also developmental and descriptive research to determine whether the problem has been addressed. The researchers used IS0 25010 to evaluate both applications. Results – Based on the result, all the case study testing was able to deliver the functionality of modules and experiments in both applications while connected to firebase database. The case study testing revealed that it is feasible to build a clinic management system that integrates a Firebase database in a Windows desktop application, providing new insight into the study.  Both applications were evaluated based on ISO 25010 with the characteristics of functional suitability, performance efficiency, compatibility, usability, reliability, security, maintainability and portability. In the Windows-based clinic management application, clinic staff scored an average of 4.37, while registered nurses scored 4.78. In the Android-based incident reporting application, a score of 4.90 was received. Conclusion – The research was able to explore the connectivity of the Window based and android based using Firebase database as a backend as a service. Based on the feedback received, both applications come out as "Excellent" in overall ISO 25010 results. Recommendations – It is recommended that future development be conducted and studied in a multiplatform desktop and mobile application connected to a Firebase database utilizing various technological tools for development. Another recommended improvement in the Windows desktop application is to integrate machine learning, given that there is ML.NET in C#, where programmers can use it in their .NET application without leaving its ecosystem. Research Implications – This study enabled the connectivity of Windows and Android-based applications using Firebase database. The system has been implemented in a school clinic, and the software's quality is being continuously improved. Keywords – firebase database, clinic management system, incident reporting, windows application, android application